The Rose That Grew from Concrete: A Study of Hip-Hop Based Education in Urban Fifth-grade Math - Lutes, Amity C. (My University, 2019)
The purpose of this study was to determine the effect of the implementation of a Hip-Hop Based Education (HHBE) Unit on fifth-grade students’ math achievements and math attitudes. This was a mixed-methods study with an explanatory sequential design. The quantitative data about student math achievements were collected using a pretest and posttest created from a county test bank and the quantitative data about student math attitudes were collected using a pre-survey and post-survey (The Math and Me Survey). Both the pretest and pre-survey were given to 113 fifth-grade student participants at a high-minority, low-income school in North Central Georgia before the implementation of the HHBE unit. After the HHBE math unit was implemented by the six participating fifth-grade teachers for four weeks, the participating students were given the posttest and post-survey. Qualitative data were collected through 452 weekly student essays and through interviews with five of the six participating teachers. The results indicated that HHBE can be a useful strategy to increase student math achievements in a high-minority, low-income school. Although student attitudes did not significantly increase based on the results from the pre-survey to post-survey, student comments on the perceptions essays showed that a majority of students did perceive that their math attitudes increased during the implementation of the HHBE unit. Teachers also expressed that the HHBE unit created a positive engagement for most students. The results of the study also provided evidence that student gender does not significantly affect the changes in student math achievements and attitudes. Finally, the results of the study provided evidence that the use of specifically designed activities, such as rap songs and “creating the raps,” are useful and culturally relevant strategies. Keywords: Hip-Hop Based Education, Urban Education, Music Education, Math Education, Culturally Responsive Teaching, Rap Songs in Education
CHAPTER I: INTRODUCTION 1 -- Problem Statement 3 -- Purpose of the Study 5 -- Research Questions 7 -- Theoretical Framework 8 -- Methodology 12 -- Significance of the Study 13 -- Assumptions, Limitations, and Delimitations 15 -- Definition of Terms 17 -- Summary 18 -- CHAPTER II: LITERATURE REVIEW 19 -- Problems in Math Achievements and Attitudes 20 -- Strategies to Improve Math Achievements and Attitudes 22 -- Culturally Responsive Pedagogy 24 -- CRP in Teacher Preparation 24 -- CRP in Math 26 -- CRP in Other Subjects 28 -- CRP and Attitudes 29 -- Hip-Hop Culture 30 -- Hip-Hop Based Education 31 -- Movement in Mathematics 35 -- Music in Mathematics 36 -- Music and Math Attitudes 39 -- Music in Education 40 -- CRP, HHBE, and Math 42 -- Gender and Math 43 -- Summary 46 -- CHAPTER III: METHODOLOGY 48 -- Research Questions 48 -- Research Design 49 -- Research Setting and Participants 50 -- Description of Intervention 52 -- Instrumentation 55 -- Quantitative Instrument 55 -- Qualitative Instrument 56 -- Validity and Reliability 58 -- Data Collection Procedure 59 -- Quantitative Data Collection 59 -- Qualitative Data Collection 61 -- Data Analysis 62 -- Quantitative Data Analysis 62 -- Qualitative Data Analysis 63 -- Data Integration 64 -- Summary 65 -- CHAPTER IV: DATA ANALYSIS 66 -- Participant Demographics 66 -- Analysis of Research Question 1 1 67 -- Analysis of Research Question 1 2 72 -- Analysis of Research Question 2 1 75 -- Analysis of Research Question 2 2 78 -- Analysis of Research Question 3 81 -- Overall Student Perceptions 82 -- Favorite Activities and Least Favorite Activities 92 -- Attitudes toward Math 102 -- Student Math Achievements 111 -- Analysis of Research Question 4 120 -- Student Engagement 122 -- Teacher Perceptions Related to Gender 124 -- Teacher Perceptions Related to Ethnicity 124 -- Teacher Perceptions Related to Culturally Responsive Teaching 125 -- Increased Student Math Achievements 126 -- The expansion of HHBE in Education 127 -- Integrating Quantitative and Qualitative Data 127 -- Overall Student Perceptions 128 -- Changes in Math Achievements 128 -- Changes in Math Attitudes 129 -- Gender Effect on Overall Student Perceptions 131 -- Gender Effect on Math Achievements 131 -- Gender Effect to Math Attitudes 132 -- Favorite Activities and Least Favorite Activities 134 -- Culturally Responsive Teaching 135 -- CHAPTER V: CONCLUSIONS, IMPLICATIONS, AND RECOMMENDATIONS 136 -- Discussions of the Findings 136 -- Implications for Practice 145 -- Recommendations for Future Research 147 -- Conclusions 148 -- REFERENCES 150 -- APPENDIX A: Unit 2 Pretest 159 -- APPENDIX B: Unit 2 Pretest Blueprint (For Teachers) 168 -- APPENDIX C: Unit 2 Posttest 170 -- APPENDIX D: Unit 2 Posttest Blueprint (For Teachers) 179 -- APPENDIX E: Math and Me Survey 181 -- APPENDIX F: Math and Me Survey Table 183 -- APPENDIX G: Math and Me Survey Permission Emails 185 -- APPENDIX H: Weekly Student Perceptions Essay Questions 187 -- APPENDIX I: Interview Guide for Teachers of HHBE Unit 189 -- APPENDIX J: HHBE Unit Timeline 191 -- APPENDIX K: Sample HHBE Lesson PowerPoint (Week1, Day1) 196 -- APPENDIX L: Sample HHBE Unit Lesson Plan (Week 1, Day 1) 201 -- APPENDIX M: VSU IRB Approval 204
Keywords: Culturally relevant pedagogy; Dissertations, Academic--United States; Education, Urban; Mathematics--Study and teaching (Elementary); Music in mathematics education; Rap (Music); Teaching